Formulasi dan Evaluasi Sediaan Blush On Powder Menggunakan Ekstrak Daging Buah Naga (Hylocereus polyrhizus) - Faneshia Nabil Ayushita; Aulia Jihan Kamila; Lubna Nurul Mumtazah; Nisrina Huwaida Isfaizah; Adriansyah Adriansyah (Journal of Educational Innovation and Public Health, 2026)
Red dragon fruit contains bioactive compounds such as vitamin C, flavonoids, and polyphenols that have antioxidant potential and possess natural pigments that can be used as cosmetic colorants. This study aims to formulate and evaluate a blush-on powder preparation from dragon fruit pulp extract as an alternative natural colorant. The evaluation includes organoleptic testing, homogeneity, pH, irritation, spreadability, fineness, moisture content, and antioxidant activity. The results showed that the formulation met most of the requirements, exhibiting a pink color, a smooth texture, no odor, homogeneity, a pH of 6 suitable for the skin, no irritation, even spreadability within 4 applications, a fineness degree of 97.6%, and a moisture content of 6.91%. Antioxidant activity showed an IC₅₀ value of 0.3036 ppm (very strong), although the relative inhibition percentage was low (18.35%). Thus, dragon fruit extract has the potential as a natural ingredient in blush-on powder that provides both color and antioxidant benefits.